2019
DOI: 10.1128/jcm.01048-19
|View full text |Cite
|
Sign up to set email alerts
|

QuantiFERON-TB Performs Better in Children, Including Infants, than in Adults with Active Tuberculosis: a Multicenter Study

Abstract: Immunological tests, including the QuantiFERON-TB Gold In-Tube (QFT-IT) assay, represent an important aid for diagnosing active tuberculosis (TB) and latent TB infections in children, but concerns about their use in children <5 years of age persist. This is a multicenter retrospective study comparing a population of 226 children to 521 adults with pulmonary or extrapulmonary TB. The aim was to evaluate the QFT-IT performance, analyzing both qualitative and quantitative results, according to age, birthplace,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 33 publications
(32 reference statements)
1
3
2
Order By: Relevance
“…Our data and others indicate that indeterminate results are more common among children than older populations (excluding adults >65 years of age in our study) ( 32 ). Impaired immunity has been independently associated with a higher probability of an indeterminate QFT-GIT ( 33 , 34 ), along with patients with active TB ( 32 ). One study suggested that T-cell based assays, such as QFT, have poor performance in children with immature or impaired immune systems ( 35 ).…”
Section: Discussionsupporting
confidence: 71%
“…Our data and others indicate that indeterminate results are more common among children than older populations (excluding adults >65 years of age in our study) ( 32 ). Impaired immunity has been independently associated with a higher probability of an indeterminate QFT-GIT ( 33 , 34 ), along with patients with active TB ( 32 ). One study suggested that T-cell based assays, such as QFT, have poor performance in children with immature or impaired immune systems ( 35 ).…”
Section: Discussionsupporting
confidence: 71%
“…Therefore, QFT-Plus is effective in children and can be a good alternative to TST ( Buonsenso et al 2020 ). This rate is much lower than that reported from previous studies on QFT assay ( Lombardi et al 2018 ; 2019 ; Kay et al 2019 ; Primaturia et al 2020 ) but higher than in this study (0.47%; 1/213). Indeterminate results mostly concerned the children with acute infections (pneumonia) and did not occur in TB children ( Lombardi et al 2018 ; 2019 ).…”
Section: Discussioncontrasting
confidence: 84%
“…This rate is much lower than that reported from previous studies on QFT assay ( Lombardi et al 2018 ; 2019 ; Kay et al 2019 ; Primaturia et al 2020 ) but higher than in this study (0.47%; 1/213). Indeterminate results mostly concerned the children with acute infections (pneumonia) and did not occur in TB children ( Lombardi et al 2018 ; 2019 ). The young age of patients did not adversely affect IGRA response, and QFT-IT positive versus negative results were not age-related ( Critselis et al 2012 ).…”
Section: Discussioncontrasting
confidence: 84%
“…TB was preferred over QFT. IGRAs are not generally recommended below two years of age, but we and others had encouraging results at this age …”
Section: Methodsmentioning
confidence: 74%